Nilai Karakter yang Terkandung dalam Buku Cerita Bergambar Karya Dini W. Tamam - Bagus Faizal Rizal; Tanzil Huda; Agus Milu Susetyo (FKIP, Universitas Palangka Raya, 2024)
A study cannot be separated from the problem that needs to be explained. The problem that arises from the background is how are the character values ​​contained in picture story books? The purpose of this study is to describe the character values ​​contained in picture story books. This type of research is qualitative. The object studied to be described is the character values ​​contained in picture story books by Dini W. Tamam. The data in this study are in the form of sentences or paragraphs containing character education values. The data were collected through documentation and analyzed with the following steps: (1) data grouping, (2) data coding, (3) inference, (4) analysis. The main tool for collecting data is a table and the researcher as the main instrument. The results of the data analysis show that the book